QUALITY CONTROL OF RADIOPHARMACEUTICALS IN MEDICAL INSTITUTIONS - G. E. Kodina; A. O. Malysheva (Разработка и регистрация лекарственных средств)
One of the major nuclear medicine agent is radiopharmaceutical (RPh) which is a composition comprising a radioactive isotope in certain chemical form. Quality control, namely the determination of radiochemical purity of radiopharmaceuticals produced in a medical institution, prior to administration to the patient is mandatory in all developed countries of the world since the mid-1980s. In our country, virtually the same procedure has been mandatory since the beginning of 2016, along with other measures, the implementation of which should guarantee the high quality and safety of nuclear medicine procedures according to the Order of the Ministry of Health of the Russian Federation from 27.04.2015 N 211n «On approval of the radiopharmaceutical preparation directly in medical institutions», which came into force from January 01, 2016. This article presents the main approaches to the implementation of quality control (determination of radiochemical purity) of radiopharmaceuticals manufactured directly in the medical institutions.